Philip Clayton and his interdisciplinary reflections on “personhood” - Sequeiros, Leandro (Razón y fe, 2022)
The concept of “person” is one of the most debated in the world of philosophy since the time of Boethius. For Philip Clayton theology faces serious difficulties when it engages in interdisciplinary debates, and traditional doctrinal language has not been effective in responding to such difficulties. The article seeks to answer the question: what place does “person” have in this reflection and what can be understood by a personal God?
Keywords: theology; philosophy; perception